Association of Clinicopathological Features With Outcome in Chondrosarcomas of the Head and Neck. (15th September 2020) - Asioli, Sofia; Ruengwanichayakun, Poosit; Zoli, Matteo; Guaraldi, Federica; Sollini, Giacomo; Greco, Paolo; Facco, Carla; Gibertoni, Dino; Jiménez, Brayan Vega; Benini, Stefania; Turri‐Zanoni, Mario; Pasquini, Ernesto; et al.
Abstract : Objective: The aim of this study is to assess the association between clinical and radiological features as well as of isocitrate dehydrogenase 1 and 2 ( IDH 1, 2) mutations with outcome in head and neck chondrosarcomas. Study Design: Retrospective study. Setting: Tertiary referral center. Methods: Clinical, histological, and molecular data of patients with head and neck chondrosarcomas treated by surgery were collected. Results: Forty‐six patients were included. The mean age at diagnosis was 56 years (range, 17‐78). The tumor originated from the skull base (52.2%), facial bones (28.2%), or laryngotracheal area (19.6%). At last follow‐up (median 52.5 months), 38 patients were alive, 30 of which were disease free, whereas 8 had died, 4 of disease progression and 4 of other causes. Fourteen (30.4%) had local recurrence and 2 (4.3%) had lung metastasis. All cases were negative for cytokeratin AE1/AE3, brachyury, and IDH1 at immunohistochemistry, while Sanger sequencing identified IDH1/2 point mutations, typically IDH1 R132C, in 9 (37.5%) tumors arising from the skull base. Margin infiltration on the surgical specimen negatively affected the outcome, whereas no correlation was identified with IDH mutation status. Conclusions: An adequate margin positively affects survival. IDH mutation status does not affect patient outcome.